Ethical and legal aspects of the use of the medicinal product ellaOne – the so-called 5-day „morning after” pill - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2015)
The article focuses on ethical and legal aspects of the use of the postcoital contraception. In November 2014, The European Medicines Agency recommended a change in classification status from prescription to non-prescription for the emergency contraceptive ellaOne. This medicinal product has been authorized in the European Union since 2009. The European Medicines Agency found that ellaOne could be used safely and effectively without medical prescription, which means that this medicinal product could be obtained without a prescription in the EU. The decision opens up a new stage of public debate about the beginnings of human life and recognition of the human embryo as a human being from the very moment of conception.